Involvement of the Vitamin D Receptor in Energy Metabolism Revealed by Profiling of Lysine Succinylome of White Adipose Tissue. Issue 1 (December 2017) - Su, Han; Lou, Yan; Fu, Yu; Zhang, Yalin; Liu, Ning; Liu, Zuwang; Zhou, Yanyan; Kong, Juan
Abstract Lysine succinylation, emerging as a novel post-translational modification, is closely related to the regulation of diverse biological processes, including many aspects of metabolism. Growing evidence suggests that low vitamin D status might exert an adverse impact on energy balance, adipogenesis and inflammation in white adipose tissue (WAT). However, whether there are any interactions between vitamin D and lysine succinylation still remains unknown. Here, combining high-affinity enrichment of lysine succinylated peptides with mass spectrometry and bioinformatics analysis, we reported the systematic profiling of the lysine succinylome, identifying 209 sites occurring on 159 proteins were up-regulated, 3 sites in 3 proteins were down-regulated in vitamin D receptor (VDR)−/− mice. Bioinformatics analysis reveals potential impacts of lysine succinylation on diverse biological processes and molecular functions, especially on carbon biotransformation, fatty acid metabolism and TCA cycle. Furthermore, eight unique motifs surrounding the succinylation sites were validated. Collectively, our findings demonstrate the first comprehensive profiling of WAT succinylome in VDR−/− mice, and provide crucial clues for further elucidating the underlying mechanisms of the involvement of the VDR in energy metabolism.